Carbon Nanotube‐Quantum Dot Nanohybrids: Coupling with Single‐Particle Control in Aqueous Solution. Issue 16 (10th February 2017) - Attanzio, Antonio; Sapelkin, Andrei; Gesuele, Felice; van der Zande, Arend; Gillin, William P.; Zheng, Ming; Palma, Matteo
Abstract : A strategy is reported for the controlled assembly of organic‐inorganic heterostructures consisting of individual single‐walled carbon nanotubes (SWCNTs) selectively coupled to single semiconductor quantum dots (QDs). The assembly in aqueous solution was controlled towards the formation of monofunctionalized SWCNT‐QD structures. Photoluminescence studies in solution, and on surfaces at the single nanohybrid level, showed evidence of electronic coupling between the two nanostructures. The ability to covalently couple heterostructures with single particle control is crucial for the design of novel QD‐based optoelectronic and light‐energy conversion devices. Abstract : A facile strategy to couple semiconductor quantum dots (QDs) to individual single‐walled carbon nanotubes (SWCNTs) with single‐particle control is presented. Evidence of electronic coupling at the single particle level is obtained for monovalent SWCNT‐QD hybrids assembled in aqueous solution via the covalent immobilization of CdSe/ZnS core/shell nanocrystals univocally at the terminal ends of individual DNA‐wrapped SWCNTs.